PERAN PEMERINTAH KABUPATEN BREBES DALAM MENANGGULANGI PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) PADA GELANDANGAN DAN PENGEMIS (STUDI KASUS DESA GRINTING) - M Zain Yaumil Akbar; Sulistyowati . (Journal of Politic and Government Studies, 2019)
This study aims to determine the problem of handling the Brebes Regency Government for homeless and beggars regarding the stigma of Grinting Village as a Beggar Village. This research use desrciptive qualitative approach. The research locations in the Social Service of Brebes Regency and Grinting Village in Bulakamba District, Brebes Regency, Central Java Province, with the consideration of many people in this area became beggars by vandalizing in Jakarta and surrounding areas.The subject of this study was determined purposively based on certain criteria, namely overcoming the stigma of begging villages embedded in Grinting Village. Data collection in this study uses interviews and in-depth document review. The collected data were analyzed using qualitative descriptive analysis techniques.This study revealed that homeless people and beggars in Grinting Village became a profession for some citizens, because they got money instantly and economic factors or poverty. Countermeasures are carried out by the government through assistance from the government and development and empowerment of village potential. Assistance provided from the Social Service is Rp. 2,000,000 per person. The development of village potential through a creative economy that has economic selling points.Keywords: The Role of the Government, Persons with Social Welfare Problems, Homelessness and Beggars, Grinting Village.